Support staff liaising effectively with family caregivers: Findings from a co-design event and recommendation for a staff training resource - Deb, Shoumitro; Limbu, Bharati (Frontiers in Psychiatry, 2022)
A high proportion of people with intellectual disabilities (ID) and autism spectrum disorder (ASD) are prescribed psychotropic medications such as antipsychotics, antidepressants etc., outside their licensed indications, primarily for the management of behaviors that challenge (BtC) in the absence of a psychiatric disorder. Examples of BtC are aggression to people and property or self-injury. BtC could be challenging to manage and may cause the person with ID/ASD and their caregivers distress, breakdown of community placement leading to hospitalization, and restrictive practices such as restraint or inappropriate medication use. Caregivers play a pivotal role in the prescribing process. However, many family caregivers feel that they have not been fully involved in the shared decision-making process about the care planning of their relatives with ID/ASD. To address the public health concern regarding the overuse of off-license prescribing in people with ID/ASD, we have recently developed a training programme called SPECTROM (Short-term Psycho-Education for Carers To Reduce OverMedication of people with intellectual disabilities) for direct care staff who support people with ID/ASD within community settings. We used co-production and a modified Experience-Based Co-Design (EBCD) method to develop SPECTROM, which involved a literature review, four focus groups and a co-design event day involving 26 stakeholders. Recommendations from the co-design event day were analyzed by a Programme Development Group (PDG) consisting of 21 stakeholders who made the final recommendations to the project team regarding the contents and the format of SPECTROM, which was finalized after receiving feedback from further 59 stakeholders. SPECTROM has web-based resources introduced through two core modules in face-to-face workshops/training. A small field test found SPECTROM was effective in improving staff's knowledge of psychotropic medications and attitude toward BtC and people with ID (p < 0.05). One of the 14 STOMP modules is “Effective liaison with family carers and advocates”. In this paper, we have presented data from the co-design event day recommendations for this particular module. The group recommended ways to improve collaborative working and effective shared decision-making with family caregivers and people with ID/ASD.